Kerusakan Dan Jumlah Hemosit Udang Windu (Penaeus monodon Fab.) Yang Mengalami Zoothamniosis [The Destruction And Total Haemocyte Count Of Penaeus monodon Fab. That Infected Zoothamnium Penaei (Zoothamniosis)] - Gunanti Maharani; Sunarti Sunarti; Juni Triastuti; Tutik Juniastuti (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract Tiger shrimp (Penaeus monodon Fab.) is one of the biggest non-oil and natural gas export fisheries commodity. In the other hand, the culture of this shrimp is highly affected by infectious pathogens and disease control is ciliated protozoa, Zoothamnium penaei that play an important role as ectocommensals on the body surface of tiger shrimp and causes "udang lumutan” disease. The aim of this research are to know the destruction and mean total haemocyte count of the Tiger shrimp between healthy and easy, middle and heavy infected degree of Zoothamnium penaei. The healthy and was identified infected Zoothamnium penaei of Tiger shrimp samples collected from one of the nursery pond in Lamongan that divided of 50 healthy indivisuals and infected Zoothamnium penaei (50 individuals for each infestation degree). Haemolymph (haemocytes) was obtained from the ventral part of the haemocoel of the second abdominal segment using 1 ml syringe filled with EDTA (Ethylene Diamine Tetra Acetic Acid). The variable observed were destruction of haemocyte and mean total haemocyte count during 7 days. ANOVA (Analysis Of Varian) was used for mean total haemocyte count change data analysis followed by Duncan's Multiple Range Test with 5% significantly. The research results revealed that Tiger shrimp that easy, middle and heavy infected of Zoothamnium penaei no destruction occurs, but Tiger shrimp that heavy infected of Zoothamnium penaei occurs haemocyte sitoplasma destruction. The highest mean total haemocyte count change was 61,64x106 ± 3,56x106 cells ml-1 in Tiger shrimp that middle infected of Zoothamnium penaei, while the lowest mean total haemocyte count change was 41,04x106 ± 3,64x106 cells ml-1 occur in Tiger shrimp that heavy infected of Zoothamnium penaei.